Clinical Findings and Antimicrobial Susceptibility of Anaerobic Bacteria Isolated in Bloodstream Infections - Fernando Cobo; Jaime Borrego; Esther Gómez; Isabel Casanovas; Elizabeth Calatrava; Carla Foronda; José María Navarro-Marí (MDPI AG, 2020)
The objectives of this study were to report on the antimicrobial susceptibility of 141 clinically significant anaerobic bacteria isolated from bloodstream infections between January 2016 and April 2020 in a tertiary-care hospital in Granada (Spain) and to describe the main clinical features of the patients. Species identification was performed by MALDI-TOF MS (Bruker Daltonics, Billerica, MA, USA). Antimicrobial susceptibility tests were performed against penicillin, amoxicillin-clavulanic acid, imipenem, moxifloxacin, clindamycin, metronidazole, and piperacillin-tazobactam using the gradient diffusion technique and EUCAST breakpoints, except for moxifloxacin (CLSI breakpoints). The most frequent anaerobes were Bacteroides (43.9%, n = 62), Clostridium (24.1%, n = 34) and Gram-positive anaerobic cocci (GPACs) (15.6%, n = 22). Almost all tested anaerobes were susceptible to imipenem and amoxicillin-clavulanic acid, except for Bacteroides. High overall resistance rates to clindamycin were observed, especially for Gram-positive anaerobic cocci (GPACs) (54.5%) and for Bacteroides spp. (45.1%). Overall, low resistance rates to almost all antibiotics were observed for Clostridium. High resistance rates to penicillin were also observed for Gram-positive anaerobic bacilli (GPABs) (44.4%), as well as to metronidazole (22.2%), although only nine isolates were included. Antimicrobial susceptibility testing for anaerobes should always be performed in severe infections, such as those localized in the bloodstream. The information obtained contributes to selecting empirical treatments according with local data on resistance.